IMPLEMENTASI PENDIDIKANKARAKTER MELALUI KEGIATANEKSTRAKURIKULER SENI TARI DI SEKOLAH DASAR NEGERI 1 TRIRENGGO TAHUNPELAJARAN2015/2016 - Yuni Sri Lestari; FX Sindhuredja (Universitas Sarjanawiyata Tamansiswa, 2016)
This research did in Elementary School 1 Trirenggo by using qualitative metode. This research had done using interview technique, observation, and documentation. The subject of this research were Headmaster of Elementary School 1 Trirenggo, coordinator teacher of traditional dancing extracurricular, and students who followed extracurricular. Researcher did data analysis by collecting data, reduction data, presentating data, and withdrawal of the conclusion. The result of this research were Character Educational Implementation by using Traditional Dancing Extracurricular in Elementary School 1 Trirenggo had made with a habitual, treatment in Traditional Dancing Extracurricular; the students had shown characteristic values when Traditional Dancing Extracurricular, support factors was the brand of school based model culture by proof SK from regent, infrastructure which enough. While obstruction factors were time and focus at one brand at Elementary School 1 Trirenggo.